Tryptophan Ameliorates Barrier Integrity and Alleviates the Inflammatory Response to Enterotoxigenic Escherichia coli K88 Through the CaSR/Rac1/PLC-γ1 Signaling Pathway in Porcine Intestinal Epithelial Cells - Liu, Guangmang; Gu, Ke; Wang, Fang; Jia, Gang; Zhao, Hua; Chen, Xiaoling; Wu, Caimei; Zhang, Ruinan; Tian, Gang; Cai, Jingyi; Tang, Jiayong; Wang, Jing (Frontiers in Immunology, 2021)
Background: Impaired intestinal barrier integrity plays a crucial role in the development of many diseases such as obesity, inflammatory bowel disease, and type 2 diabetes. Thus, protecting the intestinal barrier from pathological disruption is of great significance. Tryptophan can increase gut barrier integrity, enhance intestinal absorption, and decrease intestinal inflammation. However, the mechanism of tryptophan in decreasing intestinal barrier damage and inflammatory response remains largely unknown. The objective of this study was to test the hypothesis that tryptophan can enhance intestinal epithelial barrier integrity and decrease inflammatory response mediated by the calcium-sensing receptor (CaSR)/Ras-related C3 botulinum toxin substrate 1 (Rac1)/phospholipase Cγ1 (PLC-γ1) signaling pathway. Methods: IPEC-J2 cells were treated with or without enterotoxigenic Escherichia coli (ETEC) K88 in the absence or presence of tryptophan, CaSR inhibitor (NPS-2143), wild-type CaSR overexpression (pcDNA3.1-CaSR-WT), Rac1-siRNA, and PLC-γ1-siRNA. Results: The results showed that ETEC K88 decreased the protein concentration of occludin, zonula occludens-1 (ZO-1), claudin-1, CaSR, total Rac1, Rho family member 1 of porcine GTP-binding protein (GTP-rac1), phosphorylated phospholipase Cγ1 (p-PLC-γ1), and inositol triphosphate (IP3); suppressed the transepithelial electrical resistance (TEER); and enhanced the permeability of FITC-dextran compared with the control group. Compared with the control group, 0.7 mM tryptophan increased the protein concentration of CaSR, total Rac1, GTP-rac1, p-PLC-γ1, ZO-1, claudin-1, occludin, and IP3; elevated the TEER; and decreased the permeability of FITC-dextran and contents of interleukin-8 (IL-8) and TNF-α. However, 0.7 mM tryptophan+ETEC K88 reversed the effects induced by 0.7 mM tryptophan alone. Rac1-siRNA+tryptophan+ETEC K88 or PLC-γ1-siRNA+tryptophan+ETEC K88 reduced the TEER, increased the permeability of FITC-dextran, and improved the contents of IL-8 and TNF-α compared with tryptophan+ETEC K88. NPS2143+tryptophan+ETEC K88 decreased the TEER and the protein concentration of CaSR, total Rac1, GTP-rac1, p-PLC-γ1, ZO-1, claudin-1, occludin, and IP3; increased the permeability of FITC-dextran; and improved the contents of IL-8 and TNF-α compared with tryptophan+ETEC K88. pcDNA3.1-CaSR-WT+Rac1-siRNA+ETEC K88 and pcDNA3.1-CaSR-WT+PLC-γ1-siRNA+ETEC K88 decreased the TEER and enhanced the permeability in porcine intestine epithelial cells compared with pcDNA3.1-CaSR-WT+ETEC K88.